2019
DOI: 10.1371/journal.pone.0218352
|View full text |Cite
|
Sign up to set email alerts
|

Fall armyworm (Spodoptera frugiperda Smith) feeding elicits differential defense responses in upland and lowland switchgrass

Abstract: Switchgrass ( Panicum virgatum L.) is a low input, high biomass perennial grass being developed for the bioenergy sector. Upland and lowland cultivars can differ in their responses to insect herbivory. Fall armyworm [FAW; Spodoptera frugiperda JE Smith (Lepidoptera: Noctuidae)] is a generalist pest of many plant species and can feed on switchgrass as well. Here, in two different trials, FAW larval mass were significantly reduced when fed on lowland cultivar Kanlow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 66 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…These pathways are broadly involved in abiotic and biotic stress response in plants and have been shown to be induced by arthropod herbivory in other systems as well. For example, Palmer et al reported the upregulation of defense-related pathways including phenylpropanoid biosynthesis, flavonoid biosynthesis, and plant-hormone signal transduction in switchgrass in response to fall armyworm, Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) [ 58 ]. Further, Liang et al reported the activation of genes involved in signal transduction, flavonoid metabolism, and plant pathogen interactions potentially to have been associated with the resistance of cucumber to Aphis gossypii Glover (Hemiptera: Aphididae).…”
Section: Resultsmentioning
confidence: 99%
“…These pathways are broadly involved in abiotic and biotic stress response in plants and have been shown to be induced by arthropod herbivory in other systems as well. For example, Palmer et al reported the upregulation of defense-related pathways including phenylpropanoid biosynthesis, flavonoid biosynthesis, and plant-hormone signal transduction in switchgrass in response to fall armyworm, Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) [ 58 ]. Further, Liang et al reported the activation of genes involved in signal transduction, flavonoid metabolism, and plant pathogen interactions potentially to have been associated with the resistance of cucumber to Aphis gossypii Glover (Hemiptera: Aphididae).…”
Section: Resultsmentioning
confidence: 99%
“…It also has an annotated genome (https://phytozome. jgi.doe.gov/pz/portal.html#!info?alias=Org_Pvirgatum_er) that has facilitated a better understanding of genomic and functional genomic aspects of this plant [for example: (Dworkin et al, 2017;Taylor et al, 2018;Clifton-Brown et al, 2019;Jiang et al, 2019;Palmer et al, 2019a)]. Switchgrass occurs as upland and lowland ecotypes (Vogel et al, 2011), and some tetraploid switchgrass ecotypes differ in their susceptibility to aphids (Koch et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Switchgrass ( Panicum virgatum L.) is an herbaceous non-model species targeted for bioenergy but with important ecosystem advantages as a conservation and forage crop ( Vogel et al., 2011 ). It also has an annotated genome ( ) that has facilitated a better understanding of genomic and functional genomic aspects of this plant [for example: ( Dworkin et al., 2017 ; Taylor et al., 2018 ; Clifton-Brown et al., 2019 ; Jiang et al., 2019 ; Palmer et al., 2019a )]. Switchgrass occurs as upland and lowland ecotypes ( Vogel et al., 2011 ), and some tetraploid switchgrass ecotypes differ in their susceptibility to aphids ( Koch et al., 2014a ).…”
Section: Introductionmentioning
confidence: 99%
“…Many TF families have been identified as playing a role in response to insect herbivores in other plants [ 9 , 56 , 91 , 92 , 93 ]. Here, two members of the WRKY family (WRKY50 and WRKY70) were upregulated after aphid attacks for both cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, switchgrass cultivars often differ in their responses to biotic and abiotic stress as well [ 3 , 4 , 5 , 6 , 7 ]. Among biotic stressors that have been evaluated, differential responses to insect herbivory have been reported [ 8 , 9 , 10 , 11 ]. Plants, especially at the early stages of growth, can be susceptible to aphid infestation, although economic damage to field-grown biomass has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%